2013
DOI: 10.1017/s1041610213002019
|View full text |Cite
|
Sign up to set email alerts
|

Variability between nursing homes in prevalence of antipsychotic use in patients with dementia

Abstract: There was considerable variation between the participating LTCFs in the prevalence of APD use. Variability was related to LTCF characteristics and patient satisfaction. This indicates potential inappropriate prescribing because of differences in institutional prescribing culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 33 publications
(41 reference statements)
5
49
0
Order By: Relevance
“…A recent study found that 32% of a sample of 290 Dutch long-term care residents was prescribed an AP (van der Putten et al 2014). Similar findings were reported in the same year in a larger study (N = 1090 Dutch long-term care residents from 20 long-term care residences), where 31% long-term care residents were prescribed at least one AP drug (Kleijer et al 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A recent study found that 32% of a sample of 290 Dutch long-term care residents was prescribed an AP (van der Putten et al 2014). Similar findings were reported in the same year in a larger study (N = 1090 Dutch long-term care residents from 20 long-term care residences), where 31% long-term care residents were prescribed at least one AP drug (Kleijer et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…In the Netherlands, recent investigations of AP use in older persons has focused on institutionalised elderly persons (Sterke et al 2012;van de ven-Vakhteva et al 2013;van der Speck et al 2013;Kleijer et al 2014;van der Putten et al 2014). The prevalence of AP use in community-dwelling Dutch elderly persons with dementia in recent years has not been estimated.…”
Section: Introductionmentioning
confidence: 99%
“…The prescription rate of antipsychotics for dementia patients was reported to be 32.8% in 57 LTCFs in seven European countries and Israel, 7 and 31% in 20 LTCFs in the Netherlands. 16 However, these studies also targeted a limited number of select LTCFs, and are not 18 Facility-related factors, including the number of beds, location, ownership, and establishment of functional training and program rooms of LTCFs did not show a statistically significant difference in the antipsychotic prescription rate. Previous studies in the U.S., the Netherlands, and Canada reported that the prescription rates of antipsychotics in LTCFs differ according to the characteristics and culture at the facility level, independent of individual characteristics, even in the same country.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in the U.S., the Netherlands, and Canada reported that the prescription rates of antipsychotics in LTCFs differ according to the characteristics and culture at the facility level, independent of individual characteristics, even in the same country. 15,16,19,20 However, there are no residing physicians in Korean LTCFs. Physician visits occur every two weeks, but prescriptions within the institution are prohibited by law, and necessary prescriptions can only be issued in external hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…179,180 Indeed, there is some evidence from process notes (see Chapter 2) that the 'unofficial hierarchy' that was noted in a study of care home staff and physician interactions 104 may have undermined implementation of these action plans. Variability in the culture of some homes, with respect to antipsychotic use, 181 could have also contributed. The unwillingness of nurses and GPs to discontinue use of antipsychotics has been noted as a significant barrier to changed practice 182 where the authors suggest that these barriers may be overcome with more complex multidisciplinary interventions.…”
Section: Fidelity and Adherence To The Interventionmentioning
confidence: 99%